The Urgency of Strengthening Business License Revocation as an Administrative Sanction to Act against Violations of Workers' Normative Rights in Indonesia - Sulaiman Amiruddin; Riswadi Riswadi (Publikasi Indonesia, 2025)
Labor law enforcement in Indonesia still faces various challenges, one of which is related to the application of administrative sanctions, especially the cancellation of business permits. Law Number 6 of 2023 for Job Creation and Law Number 13 of 2003 concerning Manpower both declare that the termination of business licenses has a clear legal basis, its implementation has not been optimal. This is due to various legal, technical, and political obstacles. Therefore, this study aims to identify the urgency of strengthening the mechanism for revoking business licenses as administrative sanctions, as well as proposing strengthening strategies that include improving regulations, increasing the capacity of supervisors, optimizing the OSS system, and strengthening coordination between agencies. Strengthening this mechanism is expected to increase the effectiveness of labor law enforcement, protect workers' normative rights, create fairer and more harmonious industrial relations, and a better-quality investment climate.